The Limits of Artificial Stimuli in Behavioral Research: The Umwelt Gamble. (2nd February 2015) - Lahti, David C.; Foster, S.
Abstract The use of artificial stimuli in behavioral experimentation is pervasive and well precedented. A perspective by Hauber et al. (2014) Ethology describes advantages of this approach and highlights the use of model bird eggs and artificial egg coloration in research on egg rejection in the context of brood parasitism. Here, as a companion piece focused on quality control, I outline limitations and pitfalls associated with the use of artificial stimuli. In general, the practice makes assumptions about the perception and cognition of the study organism, therefore involving what could be called an umwelt gamble. The magnitude of this gamble and the prospects for interpretable results depend on the experimental design, the particular stimulus, and its intended role. Common roles are (1) as a representative stimulus to be generalized to a broader class; (2) as a substitute for a natural stimulus; (3) as a modification or exaggeration of natural stimuli; or (4) as an entirely novel stimulus. Whether the gamble is successful—whether the methodology navigates peculiarities of the study organism in the way the researchers intend—can be tested with controls that function as artifact detection tests. Given the propensity of animals to be biased, sometimes in unforeseen ways, in the way they perceive and interpret their environments, researchers should be careful when considering the use of artificial stimuli, weighing the advantages against the risks in any particular case.